Accounting comparability and accruals-based earnings management: Evidence on listed firms in an emerging market - Nguyen Thanh Liem (Cogent Business & Management, 2021)
Users of financial statements are in a better position to evaluate the performance of the firm in question if its accounting system and methods are comparable with those of other firms. Even though accounting comparability is markedly beneficial, the empirical studies on its impact on earnings management are scant, especially in the context of developing countries that have not applied International Financial Reporting Standards (IFRS). In the present study, we examined the association between comparability and accruals-based earnings management, considering the moderating impacts of financial constraints in the context a developing economy. The article used a sample of 502 Vietnamese non-financial listed firms from 2010 to 2019. Three proxies of comparability and two measures of accruals-based earnings manipulation, together with several empirical strategies, are employed. First, the research provides evidence suggesting that comparability reduces firms' tendency to engage in earnings management. Furthermore, there is evidence suggesting that firms could give more weighting to the comparability with a small number of firms rather than various firms in the same industry. Second, we are the first to identify that financial constraints have a moderating effect: more constrained firms do not reduce earnings manipulation as their accounting comparability improves. Based on research findings, we provided implications to stakeholders and propose directions for future studies.
Keywords: 650; accounting comparability; earnings management; financial constraints; nonlinear relationship; financial reporting quality